Analysis of Russian market of foodstuffs and agricultural raw materials in modern conditions of managing - Shabalina, L.; Kapko, A. (Економічний вісник Донбасу, 2016)
The paper analyzes the characteristics and trends in the product structure and geographical flows of Russia’s trade. A significant influence of TNCs on the Russian market of food and agricultural raw materials was detected. The developmental problems, place and prospects of Russia on the global food market in terms of import substitution policy were identified. У статті проаналізовано особливості та тенденції товарної структури та географічних потоків торгівлі Росії. Виявлено істотний вплив ТНК на російський ринок продовольства та сільськогосподарської сировини. Визначено проблеми розвитку, місце та перспективи Росії на світовому ринку продовольства в умовах політики імпортозаміщення. В статье проанализированы особенности и тенденции в товарной структуре и географических потоках торговли России. Выявлено существенное влияние ТНК на российский рынок продовольствия и сельскохозяйственного сырья. Определены проблемы развития, место и перспективы России на мировом рынке продовольствия в условиях политики импортозамещения.